Evaluation of rice genotypes for growth, yield and yield components - Shrestha, Jiban; Subedi, Sudeep; Kushwaha, Ujjawal Kumar Singh; Maharjan, Bidhya (Journal of Agriculture and Natural Resources, 2021)
Twelve rice genotypes were evaluated under irrigated lowland and upland rainfed conditions in a randomized complete block design with three replications at Khumaltar, Lalitpur, Nepal in 2019. Data on plant height, panicle length, effective tillers per plant, fertile grain number per panicle and grain yield were taken. The variation was observed for plant height, panicle length, effective tillers per plant, fertile grain number per panicle among the evaluated rice genotypes. The rice genotype NR 11375-B-B-21 produced the highest grain yield (3974.75 kg/ha) followed by NR 11374-B-B-23 (3615.26 kg/ha) and NR 11145-B-B-B-6 (3597.56 kg/ha) under irrigated low land condition. Similarly, the rice genotypes, NR 11375-B-B-21 produced the highest grain yield (3837.15 kg/ha) followed by NR 11321-B-B-7-3 (3588.71 kg/ha) and NR 11305-B-B-1-3 (3292.36 kg/ha) under upland rainfed condition. The combined analysis showed that rice genotype NR 11375-B-B-21 produced the highest grain yield (3905.95 kg/ha) followed by NR 11374-B-B-23 (3494.63 kg/ha), and NR 11321-B-B-7-3 (3409.89 kg/ha) respectively. Thus, after evaluation of yield, two genotypes namely NR 11375-B-B-21, NR 11374-B-B-23, were selected as outstanding genotypes, which can be used as potential breeding materials for upland and low land environments of mid hills of Nepal.